2013
DOI: 10.1155/2013/510392
|View full text |Cite
|
Sign up to set email alerts
|

The Medical Necessity for Medicinal Cannabis: Prospective, Observational Study Evaluating the Treatment in Cancer Patients on Supportive or Palliative Care

Abstract: Background. Cancer patients using cannabis report better influence from the plant extract than from synthetic products. However, almost all the research conducted to date has been performed with synthetic products. We followed patients with a medicinal cannabis license to evaluate the advantages and side effects of using cannabis by cancer patients. Methods. The study included two interviews based on questionnaires regarding symptoms and side effects, the first held on the day the license was issued and the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 15 publications
4
54
0
Order By: Relevance
“…These data are consistent with a recent survey of Israeli patients, in which only 50% of those who received permits were actually using cannabis six to eight weeks after commencing treatment. 18 Although some patients (i.e., those receiving adjuvant treatment) may not need renewal, our data suggest that a significant percentage of patients and/or physicians do not perceive benefit from cannabis. As expected, patients with advanced disease and those receiving supportive care only were more likely to ask for renewal.…”
Section: Discussionmentioning
confidence: 69%
“…These data are consistent with a recent survey of Israeli patients, in which only 50% of those who received permits were actually using cannabis six to eight weeks after commencing treatment. 18 Although some patients (i.e., those receiving adjuvant treatment) may not need renewal, our data suggest that a significant percentage of patients and/or physicians do not perceive benefit from cannabis. As expected, patients with advanced disease and those receiving supportive care only were more likely to ask for renewal.…”
Section: Discussionmentioning
confidence: 69%
“…Indications for both dronabinol and nabilone include the treatment of recalcitrant nausea and vomiting following chemotherapy in cancer patients. Dronabinol is also approved as an appetite stimulant in diseases such as AIDS which result in severe weight loss . (Table )…”
Section: Current Cannabinoid‐based Therapiesmentioning
confidence: 99%
“…Dronabinol is also approved as an appetite stimulant in diseases such as AIDS which result in severe weight loss. [77][78][79][80][81][82][83][84] (Table IV)…”
Section: Current Cannabinoid-based Therapiesmentioning
confidence: 99%
“…[2][3][4] Two of the most commonly reported risks are dependence and an increased risk of motor vehicle accidents. [9][10][11] The increasing evidence base for therapeutic effects, along with public pressure, has led to the implementation of medical cannabis policies in various jurisdictions, including Israel, Canada, and the Netherlands, as well as 23 states in the United States. [9][10][11] The increasing evidence base for therapeutic effects, along with public pressure, has led to the implementation of medical cannabis policies in various jurisdictions, including Israel, Canada, and the Netherlands, as well as 23 states in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from Israel have found that between 13% to 25% of oncology patients treated with medical cannabis died approximately 4 to 8 weeks after receiving the license, 9,10 and 12% of patients withdrew from treatment with medical cannabis within a week due to negative side effects or the absence of clinical improvement. Oncology patients can be granted medical cannabis licenses for 1 of 2 indications: to reduce chemotherapy-induced symptoms (after exhaustive unsuccessful relief through traditional treatments) and as palliative care.…”
Section: Introductionmentioning
confidence: 99%